Plate and faults boundary detection using gravity disturbance and Bouguer gravity anomaly from space geodesy - Atriyon Julzarika; Argo Galih Suhadha; Indah Prasasti (Sustinere: Journal of Environment and Sustainability, 2020)
Nowadays, satellite technology has developed significantly. Geodesy satellites such as Grace and Grace-FO can be used for subsurface mapping. The mapping is in the form of detection of the plate details, faults, and regional geodynamic conditions. This study aims to detect plate and faults from space geodesy using the gravity disturbance and Bouguer gravity anomaly parameter. The study area is in the Sunda Strait. Gravity disturbance is one of the gravity model parameters. Gravity disturbance is the gravitational potential of the topography expressed by the spherical harmonic model and the topographic effect by Barthelmes's calculations. Gravity disturbance can visualize subsurface conditions. Bouguer gravity anomaly is needed to get the condition on subsurface objects. This parameter visualizes subsurface conditions in the form of rocks and non-rocks. These conditions can distinguish oceanic crust and continental crust. Gravity contours are needed to obtain plate and faults predictions. The results obtained are validated patterns and shapes with plate and faults secondary data. The tolerance used in this validation is 80%. The gravity disturbance parameter obtained a value of 83% in verifying the accuracy of assessment in plate and faults detection. The Bouguer gravity disturbance parameter obtained a verification value of accuracy assessment in plate detection but 65% in faults detection. This accuracy assessment uses pattern and texture parameters in detecting the similarity of two or more images. This plate and faults detection results are more detailed and can be used for geophysical, geological, earthquake, and earth dynamics applications.